Australia's Uranium - Resources, Production, and Demand in World Perspective - McKay AD (The Australasian Institute of Mining and Metallurgy, 1986)
The bulk of Australia's uranium resour- ces was delineated in the last 18 years when a total of $563 million (1984 dollar values) was spent on uranium exploration. Australia's share of the low-cost Reasonably Assured Re- sources in the World Outside the Centrally Planned Economies Area (WOCA) increased from 1.5% in 1967 to 29% by the end of 1984 and its share of the low-cost Estimated Additional Resources (Category I) then stood at 25%. As of December 1984, Australia's uranium resour- ces were estimated by the BMR to be: Cost range US$80/kg U (US$30/lb U301) Reasonably Assured Resources 463 000 t U Estimated Additional Resources(I) 251 000 t U Cost range US$80-130/kg U (US$30-50/lb U308) Reasonably Assured Resources 63 000 t U Estimated Additional Resources(I) 126 000 t U The increases in Australia's resources was sustained by a group of large and rela- tively high-grade deposits which were disco- vered during the period 1969 to 1975. Austra- lia's share of the low-cost resources was also enhanced by a contraction of WOCA's low-cost resource base due to escalation of production costs for smaller low-grade deposits. Most of Australia's uranium resources are contained in the Proterozoic unconformity- type deposits of the Alligator Rivers uranium field and the stratabound deposit at Olympic Dam on the Stuart Shelf. Most of the remain- der of Australia's uranium resources is con- tained in calcrete-type deposits. Less than 10% of Australia's uranium resources are in sandstone-type deposits. Total Australian production to the end of 1984 amounted to 26 241 t U, representing 3.4% of WOCA's cumulative production. Aus- tralia's share of WOCA's annual production has steadily increased from 1.3% in 1977 to 11.2% in 1984 (4390 t U). The increases in Austra- lian production took place in the face of reductions of production in WOCA countries, principally the US, from a record level of 43 988 t U in 1980 to about 39 000 t U in 1984. New low-cost production centres, mainly in Australia and Canada, have partly compen- sated the decline in US production. The Department of Resources and Energy (1985) reported that Australian exports of yellowcake are expected to reach 10 000 t U308 (8480 t U) by 1993/94, representing an in- crease of about 13% oer annum.